PROSPECTS FOR THE DEVELOPMENT OF THE GREEN ECONOMY BASED ON INVESTMENT PROJECTS IN COOPERATION WITH DEVELOPED COUNTRIES - Adilov Mirkomil Miralimovich; Professor Suyunov Dilmurod Kholmurodovich; Associate Professor Alimov Bakhodir Batirovich (Western European Studies, 2023)
In this scientific article, the terms "investment projects" and "green economy" are defined by scientists of the world and our country. The role of investment projects and "Green economy" projects in achieving the goals set in the development strategy is indicated. At the same time, the status of investment projects attracted by foreign investors in the direction of "Green economy" is presented in full
Keywords: investment projects; green; Project